Graphene: A Reusable Substrate for Unprecedented Adsorption of Pesticides. Issue 2 (24th September 2012) - Maliyekkal, Shihabudheen M.; Sreeprasad, T. S.; Krishnan, Deepti; Kouser, Summayya; Mishra, Abhishek Kumar; Waghmare, Umesh V.; Pradeep, T.
Abstract Unprecedented adsorption of chlorpyrifos (CP), endosulfan (ES), and malathion (ML) onto graphene oxide (GO) and reduced graphene oxide (RGO) from water is reported. The observed adsorption capacities of CP, ES, and ML are as high as ∼1200, 1100, and 800 mg g−1, respectively. Adsorption is found to be insensitive to pH or background ions. The adsorbent is reusable and can be applied in the field with suitable modifications. A first‐principles pseudopotential‐based density functional analysis of graphene–water–pesticide interactions showed that the adsorption is mediated through water, while direct interactions between graphene and the pesticides is rather weak or unlikely.